Thermal Comfort for Urban Parks in Subtropics: Understanding Visitor’s Perceptions, Behavior and Attendance - Chuang-Hung Lin; Tzu-Ping Lin; Ruey-Lung Hwang (Advances in Meteorology)
The paper is an effort toward thermal comfort assessment for urban parks under the climatic conditions of Taiwan to help architects achieve better climatic design. Field interviews, observations, and micrometeorological measurements were conducted in this study. The WBGT was used as the thermophysiological index to investigate the effects of thermal conditions on visitor’s thermal perception and adaptive behavior in outdoor urban spaces. In this study, behavioral adaptations used by visitors as a means of achieving comfort were evaluated. Observational results showed that the overall attendance was influenced by sun and thermal conditions. There was a robust relationship between thermal sensation votes, as well as thermal acceptability, and thermal environment, in terms of WBGT. The upper and lower limits of 80% acceptability are 26°C WBGT and 20°C WBGT, respectively.